Pembrolizumab versus ipilimumab for advanced melanoma: final overall survival results of a multicentre, randomised, open-label phase 3 study (KEYNOTE-006). Issue 10105 (21st October 2017) - Schachter, Jacob; Ribas, Antoni; Long, Georgina V; Arance, Ana; Grob, Jean-Jacques; Mortier, Laurent; Daud, Adil; Carlino, Matteo S; McNeil, Catriona; Lotem, Michal; Larkin, James; Lorigan, Paul; et al.
Summary: Background: Interim analyses of the phase 3 KEYNOTE-006 study showed superior overall and progression-free survival of pembrolizumab versus ipilimumab in patients with advanced melanoma. We present the final protocol-specified survival analysis. Methods: In this multicentre, open-label, randomised, phase 3 trial, we recruited patients from 87 academic institutions, hospitals, and cancer centres in 16 countries (Australia, Austria, Belgium, Canada, Chile, Colombia, France, Germany, Israel, Netherlands, New Zealand, Norway, Spain, Sweden, UK, and USA). We randomly assigned participants (1:1:1) to one of two dose regimens of pembrolizumab, or one regimen of ipilimumab, using a centralised, computer-generated allocation schedule. Treatment assignments used blocked randomisation within strata. Eligible patients were at least 18 years old, with an Eastern Cooperative Oncology Group (ECOG) performance status of 0 or 1, at least one measurable lesion per Response Evaluation Criteria In Solid Tumors version 1.1 (RECIST v1.1), unresectable stage III or IV melanoma (excluding ocular melanoma), and up to one previous systemic therapy (excluding anti-CTLA-4, PD-1, or PD-L1 agents). Secondary eligibility criteria are described later. Patients were excluded if they had active brain metastases or active autoimmune disease requiring systemic steroids. The primary outcome was overall survival (defined as the time from randomisation to death from any cause). Response was assessed per RECIST v1.1 by independent central review at week 12, then every 6 weeks up to week 48, and then every 12 weeks thereafter. Survival was assessed every 12 weeks, and final analysis occurred after all patients were followed up for at least 21 months. Primary analysis was done on the intention-to-treat population (all randomly assigned patients) and safety analyses were done in the treated population (all randomly assigned patients who received at least one dose of study treatment). Data cutoff date for this analysis was Dec 3, 2015. This study was registered withClinicalTrials.gov, numberNCT01866319 . Findings: Between Sept 18, 2013, and March 3, 2014, 834 patients with advanced melanoma were enrolled and randomly assigned to receive intravenous pembrolizumab every 2 weeks (n=279), intravenous pembrolizumab every 3 weeks (n=277), or intravenous ipilimumab every 3 weeks (ipilimumab for four doses; n=278). One patient in the pembrolizumab 2 week group and 22 patients in the ipilimumab group withdrew consent and did not receive treatment. A total of 811 patients received at least one dose of study treatment. Median follow-up was 22·9 months; 383 patients died. Median overall survival was not reached in either pembrolizumab group and was 16·0 months with ipilimumab (hazard ratio [HR] 0·68, 95% CI 0·53–0·87 for pembrolizumab every 2 weeks vs ipilimumab; p=0·0009 and 0·68, 0·53–0·86 for pembrolizumab every 3 weeks vs ipilimumab; p=0·0008). 24-month overall survival rate was 55% in the 2-week group, 55% in the 3-week group, and 43% in the ipilimumab group. Interpretation: Substantiating the results of the interim analyses of KEYNOTE-006, pembrolizumab continued to provide superior overall survival versus ipilimumab, with no difference between pembrolizumab dosing schedules. These conclusions further support the use of pembrolizumab as a standard of care for advanced melanoma. Funding: Merck & Co.